PEMODELAN DISTRIBUSI KESESUAIAN HABITAT SINGGAH SIKEP MADU ASIA (Pernis ptilorhynchus) DI PULAU RUPAT BERDASARKAN DATA SATELLITE- TRACKING - Hendry Pramono; Yeni Aryati Mulyani; Syartinilia .; Higuschi . (Department of Forest Resources Conservation and Ecotourism - IPB University, 2015)
Birds of prey are one of environmental changes indicators because of their position as top predator. Many of them are migratory species that migrate from northern hemisphere to southern hemisphere, and use Rupat Island (in Riau Province) as stopover habitat. One of them is Oriental Honey Buzzard (Pernis ptilorhynchus) whose satellite tracking information (from 2006-2009) are available. This study aimed at identifying distribution characteristics of stopover habitats of Oriental Honey-buzzard in Rupat Island based on satellite tracking data using geographic information system (GIS). Several environmental variables (i.e. slope, elevation, land cover) were processed into distance to the nearest map and analyzed using logistic regression analysis. The result showed that distribution of stopover habitats covered 1 276.67 km2 (87%) of totally Rupat Island (1 461.95 km2). This distribution was mostly influenced by food availability and thermal wind. Identification of these habitat characteristics provides a baseline data for managing their stopover habitats and ecologically-based development of Rupat Island. Keywords: Logistic Regretion, Pernis ptilorhynchus, Rupat Island, Sattelite-tracking, Stopover habitat characteristic